Minstrels and minstrelsy in late medieval England - Rastall, Richard; Taylor, Andrew (Boydell Pres, an imprint of Boydell & Brewer, 2023)
A major new study piecing together the intriguing but fragmentary evidence surrounding the lives of minstrels to highlight how these seemingly peripheral figures were keenly involved with all aspects of late medieval communities.